Vascular injury biomarkers and stroke risk: a population-based study - Pletsch-Borba, Laura; Grafetstätter, Mirja; Hüsing, Anika; Johnson, Theron S.; González Maldonado, Sandra; Groß-Weissmann, Marie-Luise; Kloss, Manja; Hoffmeister, Michael; Bugert, Peter; Kaaks, Rudolf; Kühn, Tilman (Neurology, 2020)
OBJECTIVE: Because little is known about associations between biomarkers of vascular injury and stroke risk, we evaluated associations between plasma concentrations of 6 novel biomarkers of vascular injury and stroke risk in a population-based study. - METHODS: A case-cohort subset of EPIC-Heidelberg (European Prospective Investigation for Cancer and Nutrition-Heidelberg) including incident stroke cases (n = 335) and a random subcohort (n = 2,418) was selected. Concentrations of intercellular adhesion molecule 3 (ICAM3), soluble E-selectin and P-selectin, soluble thrombomodulin (sTM), thrombopoietin, and glycoprotein IIb/IIIa were measured in baseline plasma samples. Weighted Cox regression analyses were used to assess associations between biomarker levels and stroke risk. - RESULTS: Median follow-up in the subcohort and among cases was 9.8 (range, 0.1-12.5) years and 6.2 (range, 0.01-12.1) years, respectively. ICAM3 levels were associated with increased risk of incident stroke after multivariable adjustment (hazard ratio, highest vs lowest quartile: 1.64 [95% confidence interval, 1.15-2.32]; plinear trend < 0.001). This association was more apparent for ischemic (1.65 [1.12-2.45]; plinear trend < 0.01) than for hemorrhagic stroke (1.29 [0.60-2.78]; plinear trend = 0.3). We further observed a borderline significant trend for a positive association between sTM and overall stroke risk (1.47 [0.99-2.19]; plinear trend = 0.05). - CONCLUSIONS: In this population-based study, circulating levels of ICAM3, an adhesion molecule shed by leukocytes, were associated with increased risk of incident stroke. Further mechanistic studies are needed to elucidate the pathophysiology underlying this association. - CLASSIFICATION OF EVIDENCE: This study provides Class II evidence that plasma levels of ICAM3 are associated with increased stroke risk.
Gesehen am 01.09.2020